Distributive justice and access to advantage : G.A. Cohen's egalitarianism - Kaufman, Alexander, 1958- (Cambridge University Press, 2014)
"G. A. Cohen was one of the world's leading political theorists. He was noted, in particular, for his contributions to the literature of egalitarian justice. Cohen's classic writings offer one of the most influential responses to the currency of the egalitarian justice question - the question, that is, of whether egalitarians should seek to equalize welfare, resources, opportunity, or some other indicator of well-being. Underlying Cohen's argument is the intuition that the purpose of egalitarianism is to eliminate disadvantage for which it is inappropriate to hold the person responsible. His argument therefore focuses on the appropriate role of considerations regarding responsibility in egalitarian judgment. This volume comprises chapters by major scholars addressing and responding both to Cohen's account of the currency of egalitarian justice and its practical implications and to Cohen's arguments regarding the appropriate form of justificatory arguments about justice"--